2017
DOI: 10.1007/s11356-017-8392-z
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic effect of aluminum and ionizing radiation upon ultrastructure, oxidative stress and apoptotic alterations in Paneth cells of rat intestine

Abstract: The original publication of this paper contains an error. Abstract sentence number 5 should be: Ileum malondialdehyde, advanced oxidative protein products, protein carbonyl and tumor necrosis factor-alpha were assessed as biomarkers of lipid peroxidation, protein oxidation and inflammation respectively along with superoxide dismut-ase, catalase, and glutathione peroxidase activities as enzy-matic antioxidants. Abstract sentence number 8 should be: Oxidative and inflammatory stresses assessment in the ileum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…[ 16 ] In addition, electron micrograph exhibited that Al induced the injuries of epithelial cells, abnormal crypt, and increased bacterial invasions in small intestine. [ 17 ] In the present study, firstly, the morphological influence of Al was investigated in intestinal mucosa of mice. Our results showed that Al exposure induced abnormal intestinal barrier histological changes, including crypt abscesses, hyperplasia, and villous shorter, as well as inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] In addition, electron micrograph exhibited that Al induced the injuries of epithelial cells, abnormal crypt, and increased bacterial invasions in small intestine. [ 17 ] In the present study, firstly, the morphological influence of Al was investigated in intestinal mucosa of mice. Our results showed that Al exposure induced abnormal intestinal barrier histological changes, including crypt abscesses, hyperplasia, and villous shorter, as well as inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it must be noted that this preliminary study presented here, lacks an exploration of other important factors that mediate radiation enteritis, such as the destruction of the intestinal epithelial barrier and tight junction after irradiation exposure [12,44]. Besides, irradiation exposure not only acts as a proinflammatory signal [5,45], but also mediates oxidative and nitrative stress to induce the production of ROS and NOS in the small intestine [7,9,46,47]. In addition, GL has been reported to possess anti-oxidant properties in a recent study [48].…”
Section: Discussionmentioning
confidence: 95%
“…Reactive oxygen species represent a risk factor for the development of CRC, as they cause oxidative damage to the intestinal mucosa cells, leading to the breakdown of the intestinal barrier and its dysfunction. Oxidative damage leads to abnormal Paneth cell morphology, the dilatation of the crypt lumen and erosion of its villi, and an increase in the apoptosis of crypt cells and homogeneously electron-lucent granules [ 150 , 151 ], which creates an entry gate for pathogenic microorganisms. The disruption of the barrier triggers the invasion of commensal and pathogenic microorganisms and leads to contact between intestinal epithelial cells and components of the microbiota, which may have protumorigenic properties [ 10 ].…”
Section: Colorectal Carcinoma As a Multilevel Cancer Diseasementioning
confidence: 99%